PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS XII MIPA MAN LUWU MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) - Sitti Aliyah Rahman (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
The purpose of this research is to 1) find out the use of the PBI learning model in improving the mathematics learning outcomes of class XII MIPA MAN Luwu students. 2) To find out the increase in mathematics learning outcomes of class XII MIPA MAN Luwu after applying learning with the PBI learning model. The research method used was classroom action research on class XII MIPA MAN Luwu students, with a total of 30 students. The instruments used are student worksheets for each cycle, formative tests for each cycle, final tests, and observation sheets for student learning activities.Based on the results of the analysis of this research data, it shows that the results of students “mathematics learning with the PBI learning model have increased in each cycle. In the first cycle, the completeness of student learning outcomes reached 22 students or 73,33 %. This increased in cycle II, reaching 30 students or 100% classically fulfilling complete learning. Meanwhile student activities also experienced an increase from cycle I: 68,75 to cycle II: 89,16%. Based on the results of the research, learning mathematich with the PBI learning model is able to improve students learning outcomes in mathematics. Keywords: Learning Outcomes, Problem-Based Instruction (PBI) Learning Model.